Odpowiedź:
Szczegółowe wyjaśnienie:
a) 6^(-3) *6^5 = 6² = 36
b) 4^(-8) *4^6 = 4^(-2) = 1/16
c) 0,5^(-4) *0,5^(-1) = 0,5^(-5)
d) 5^7 : 5^10 = 5^(-3)
e) 7^(-4) : 7^(-6) = 7² = 49
f) (3^6)^(-2) = 3^(-12)
g) (6^(-2))^5 *6^8 = 6^(-10) * 6^8 = 6^(-2) = 1/36
h) [4^(-3)]^(-4) : 4^9 = 4^12 : 4^9 = 4³ = 64
i) 9^(3/2) = (3²)^(3/2) = 3³ = 27
j) 8^(-4/3) = (2³)^(-4/3) = 2^(-4) = 1/16
k) 144^(-0,5) = 144^(-1/2) = 1/12
l) 81^(-0,125) = 81^(-1/8) = [(81)^(1/4)]^(-1/2) = 3^(-1/2) = 1/√3
m) 2^(5/2) *√2 = 2^(5/2) * 2^(1/2) = 2 ^(6/2) = 2³ = 8
n) 49^(1/2) : 49^(1/4) = 49^(1/4) = 7^(1/2) = √7
o) (√7)^5 * 7^(-3/2) = 7^(5/2) * 7^(-3/2) = 7^(2/2) = 7
p) 9^(-3/4) : 27^(-3/2) = 3^(-6/4) : 3^(-9/2) = 3^(-3/2 + 9/2) =
3^(6/2) = 3³ = 27
ufff !, mam nadzieję, że się nigdzie nie pomyliłem :)